Auditoría de gestión en la Agrícola Bananera Dánica Fruits S.A. del cantón Valencia provincia de Los Ríos, periodo 2021. - Arellano Espinoza, Kerly Marisol (2023)
The Audit in the Agricultural Banana Company DANICA FRUITS S.A. in Valencia, used a descriptive, and documentary bibliographical research for the structure of the theoretical framework. On the one hand, among the information collection techniques there was an interview that was applied to the owner and the survey for the personnel who work in the company, among the methods of information analysis there was the synthetic analytical method with which once the information was analyzed, conclusions were issued. On the other hand, an internal control questionnaire was applied in which the main findings were obtained, among which the lack of implementation of administrative policies, low planning of activities, as well as a lack of definition of the company's values stand out. , there is a lack of an organizational structure, it exists under control of the activities, in addition, it is observed that they do not have a risk map nor there are active contingency plans, lack of coordination between the employees of the areas and adequate follow-up is not given when there are deficiencies in the activities carried out. The evaluation of the confidence level now has a value of 72.5%, considered moderate, a level of control risk of 11% low, and an Inherent Risk of 27.5%, qualifying as moderate based on the levels of risk and confidence. Based on the situational diagnosis carried out in the results are that one of the main strengths of the company is its own infrastructure, experience in the agricultural area; among the opportunities, it generates a large number of sources of work for the population; among the weaknesses is the lack commitment of the employees, as well as the lack of a manual of functions